WADIAH VS JU’ALAH PADA SERTIFIKAT BANK INDONESIA SYARIAH - Gulo, Melva Vicensia (Jurnal Akuntansi AKUNESA, 2013)
Bank Indonesia Sharia Certificates have a contribution to manage in monetary system. The first certificate is namedWadiah Certificates of Bank Indonesia (SWBI) with wadiah contract. But, in 2008, Bank Indonesia published regulation No: 10/11/PBI/2008 to change SWBI with Bank Indonesia Sharia Certificates (SBIS) by using ju?alah contract. The reason is return of SWBI with wadiah contract is lower than return of SBIS with ju?alah contract according to Bank Indonesia. But in another hand, there are instrument of banking still exist with wadiah contract like Tabungan Wadiah and Giro Wadiah. Considering the problem, the researcher would like to know whether the return of implementation wadiah is lower than return ju?alah. The results are return of wadiah is higher than ju?alah and implementation wadiah contract in Tabungan Wadiah and Giro Wadiah is exact base Islamic law. So, exchange this contract is needed to reconsider. Keywords : Bank Indonesia Sharia Certificates, Wadiah Certificates of Bank Indonesia, Wadiah, Ju?alah, return.